A legal study on gamete donation: the necessity for a formal regulation on gamete donation in Malaysia / Nur Izatul Fatiha Mohd Ali Hanafiah, Ommunajah Ramli and Norulashikin Mohammad Sopian. - Mohd Ali Hanafiah, Nur Izatul Fatiha; Ramli, Ommunajah; Mohammad Sopian, Norulashikin (Faculty of Law, 2011)
Infertility is one of the medical problems that happened among spouses which cause the incapability to conceive pregnancy after a year of unprotected sexual intercourse. Due to the advancement in medical field, the problem of infertility also has grabbed the attention of the medical expert to find the solution. Nevertheless, the current development in reproduction medicine had successfully found the ways in assisting the infertile couple to conceive without depending on sexual acts only. Gamete donation, one of the method in assisting infertile couple is a process where the gametes (sperm, ovum or embryo) from the third party or donor being used to conceive pregnancy. In this research paper, the study is within the scope of the practice of gamete donation among the Malaysian. The discussion in this research is about the legal position of the practice of gamete donation and the challenges on the use of gamete donation in Malaysia. As for legal position, the examination on rules, regulations and policies are being observed in order to obtain a clear picture on the position of the practice of gamete donation in Malaysia. Amongst the rules, regulations and policies are Human Tissues Act 1974, Medical Act 1971, The National Organ, Tissue and Cell Transplantation Policy, The National Population and Family Development Board (NPFDB) of the Prime Minister's Department, Guidelines by Malaysian Medical Council (MMC), guidelines of private fertility centers and etc. By examining all these legislations, it can be concluded that in Malaysia there is no law which particularly govern the practice of gamete donation. Apart from that, the discussion in this project paper is being extended on the challenges on the use of gamete donation in Malaysia. Among the major issues being discussed are human rights and religions perspectives which have influential basis for the practice of gamete donation among Malaysia citizens. These two perspectives also show that there is an existence of inconsistency among them. For example, the Muslim teaching disallow the practice of donated gamete in order to preserve the importance of lineage but the restraint of it may lead to the infringement of basic human right, which is the right to have family ( child ) and also autonomy of one's body. In addition, there are many other issues being touched such as the unethical procedure and practice by private fertility center, the exploitation of gamete, donor and infertile couple which may include the issues of commodification, commercialization and etc. These issues being elaborated in order to show that there are many defects of practice of gamete donation. These issues are appear due to the fact that the practice of gamete donation in Malaysia is largely unregulated.Therefore, this research is aimed to analyze the necessity of law enforcement regarding gamete donation in Malaysia.